The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acscatal.2c00759
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating Coordination Structures of Mixed-Valence Copper Single Atoms on 1T-MoS2 for Efficient Hydrogen Evolution

Abstract: Directing single atoms (SAs) to occupy specific lattice sites in support materials and correlating the resulting changes in atomic coordination structures to catalytic activity are crucial for the rational design of high-performance single-atom catalysts (SACs). Herein, for the same copper (Cu) SAs, two coordination structures on 1T-phase molybdenum disulfide (MoS2) are identified. In the adsorption model, Cu SAs are coordinated onto the outermost sulfur (S) plane in a trigonal pyramidal geometry (Cuads@MoS2),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…As expected, the Tafel slope of CS‐2 (201 mV dec −1 ) was smaller than SnO 2 (229 mV dec −1 ) and g‐C 3 N 4 (211 mV dec −1 ), revealing that the sluggish hydrogen evolution kinetics had been significantly accelerated after the heterojunction formed (Figure S14c , Supporting Information). [ 52 , 53 , 54 ] The photoelectrochemical performances of other composite samples were also compared to illustrate the effect of g‐C 3 N 4 content. The CS‐2 showed the highest current density among three composites.…”
Section: Resultsmentioning
confidence: 99%
“…As expected, the Tafel slope of CS‐2 (201 mV dec −1 ) was smaller than SnO 2 (229 mV dec −1 ) and g‐C 3 N 4 (211 mV dec −1 ), revealing that the sluggish hydrogen evolution kinetics had been significantly accelerated after the heterojunction formed (Figure S14c , Supporting Information). [ 52 , 53 , 54 ] The photoelectrochemical performances of other composite samples were also compared to illustrate the effect of g‐C 3 N 4 content. The CS‐2 showed the highest current density among three composites.…”
Section: Resultsmentioning
confidence: 99%
“… 37 Li et al reported the ability to enhance the HER performance of 1T-MoS 2 by either substituting lattice sites with copper (Cu) SAs or adsorbing Cu SAs along the 1T-MoS 2 basal plane. 38 Each of these methods of stabilizing Cu SAs was achieved by employing syringe injection and hydrothermal synthetic methods, respectively. Meanwhile, in a volcano plot reported by Deng et al, Zn demonstrated a Δ G H* value near 0 eV, indicating that it is one of the few nonprecious metals that may be able to modify the HER activity of MoS 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al discovered that hydrothermally synthesizing 1T-MoS 2 with Fe, Co, and Ni enhances HER activity in alkaline media by doping the guest metals into the 1T-MoS 2 lattice in a 1:6 X:Mo ratio (X = Fe, Co, or Ni) . Li et al reported the ability to enhance the HER performance of 1T-MoS 2 by either substituting lattice sites with copper (Cu) SAs or adsorbing Cu SAs along the 1T-MoS 2 basal plane . Each of these methods of stabilizing Cu SAs was achieved by employing syringe injection and hydrothermal synthetic methods, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…However, since the catalytically active sites of MoS 2 are usually located in a few edge positions, resulting in catalytic inertness at most of the exposed sites, which also leads to its low catalytic activity. 15 Besides, severe aggregation and unsatisfactory electrical conductivity further hinder the enhancement of HER activity. 16 Therefore, there is an urgent need to find out how the activity of the base surface can avoid aggregation and enhance conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…(2) Many 2D materials themselves are good electrocatalysts for HER, such as molybdenum disulfide (MoS 2 ). However, since the catalytically active sites of MoS 2 are usually located in a few edge positions, resulting in catalytic inertness at most of the exposed sites, which also leads to its low catalytic activity . Besides, severe aggregation and unsatisfactory electrical conductivity further hinder the enhancement of HER activity .…”
Section: Introductionmentioning
confidence: 99%